Synthesis, characterization and application of wheat bran/zinc aluminium and tea leaves waste/zinc aluminium biocomposites: kinetics and thermodynamics modeling. Issue 53 (13th November 2016) - Safa, Yusra; Bhatti, Haq Nawaz; Sultan, Misbah; Sadaf, Sana
Abstract: In the current study, synthesis and application of wheat bran/zinc aluminum biocomposite and tea leaves waste/zinc aluminum biocomposite for the elimination of hazardous dyes (Reactive Yellow-41 and Direct Blue-7, respectively) were examined. Diverse parameters were used for the data. Optimum pH for maximum removal of dyes was 4. Dye removal was maximum with increase in biocomposite dose, dye concentration, and temperature. The optimum contact time was detected to be 90 min for Reactive Yellow-41 onto wheat bran/zinc aluminum biocomposite and 120 min for Direct Blue-7 onto tea leaves waste/zinc aluminum biocomposite. The research data were best fitted to Langmuir isotherm and pseudo-second-order kinetic model. Surface sorption of dyes was observed through FT-IR analysis. The changes in surface morphology of both the biocomposites were investigated through SEM. XRD analysis was used to examine the crystallinity of biocomposite. It was inferred that wheat bran/zinc aluminum biocomposite and tea leaves waste/zinc aluminum biocomposite are excellent biosorbents for the removal of dyes from aqueous solutions.